Implementasi Asesmen dalam Kurikulum Merdeka pada Jenjang Sekolah Dasar - Tasya Aprillia Hadi, Anas; Sulistyowati; Hikmah, Nurul (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the implementation of assessment within the Kurikulum Merdeka at the elementary school level, with a particular focus on the application of diagnostic, formative, and summative assessments in science learning at SDIT Al-Furqan Palangka Raya. Assessment in the Independent Curriculum is designed not only to evaluate learning outcomes but also to provide a comprehensive understanding of students’ abilities, learning needs, and development potential. This research employed a qualitative descriptive method, involving the school principal and sixth-grade science teachers as participants. Data were collected through observation, interviews, and documentation, and were analyzed using the stages of data reduction, data display, and conclusion drawing. The results of the study show that assessment practices at SDIT Al-Furqan Palangka Raya have been aligned with the principles of the Kurikulum Merdeka. Diagnostic assessments are conducted at the beginning of the semester to map students’ initial competencies as the basis for differentiated instruction. Formative assessments are implemented continuously during the learning process and function as feedback for improving instructional strategies. Summative assessments are carried out at the end of the semester to measure learning achievement. These findings indicate that assessment serves as an authentic and meaningful learning instrument that supports competency development, reflective learning, and holistic student growth.